Cryptology and network security : 14th International Conference, CANS 2015, Marrakesh, Morocco, December 10-12, 2015, proceedings /: 14th International Conference, CANS 2015, Marrakesh, Morocco, December 10-12, 2015, proceedings. (2015) - Unknown
No abstract available